Desenvolvimento de um protótipo de bancada para medição e análise do fator de potência utilizando osciloscópio aplicado ao ensino de física - Marton, Ítalo Leonardo de Alencar (2017)
In this work a workbench was created for the measurement of the power factor of a load connected to the electric grid, through an oscilloscope, aiming the high school and higher education of related areas, where it is involved to several subjects that may be discussed through the experiment as: waves, alternating current power, instrumentation, resistive circuits, capacitive circuits, inductive circuits, power systems, power factor correction, distribution systems and so on. It is a simple experiment to be implemented, built with materials that are present in the daily life of the students, although with broad concepts. As a result, we have a script of the practice to be performed and the concepts involved, which may be used by teachers to complement the content studied in the classroom and improve student learning.